A nonlinear vibration isolator achieving high-static-low-dynamic stiffness and tunable anti-resonance frequency band. (1st December 2016) - Sun, Xiuting; Jing, Xingjian
Abstract: This study investigates theoretically and experimentally a vibration isolator constructed by an n-layer Scissor-Like Structure (SLS), focusing on the analysis and design of nonlinear stiffness and damping characteristics for advantageous isolation performance in both orthogonal directions. With the mathematical modeling, the influence incurred by different structural parameters on system isolation performance is studied. It is shown that, (a) nonlinear high-static-low-dynamic stiffness and damping characteristics can be seen such that the system can achieve good isolation performance in both directions, (b) an anti-resonance frequency band exists due to the coupling effect between the linear and nonlinear stiffness in the two orthogonal directions within the structure, and (c) all these performances are designable with several structural parameters. The advantages of the proposed system are shown through comparisons with an existing quasi-zero-stiffness vibration isolator (QZS-VI) and a traditional mass-spring-damper vibration isolator (MSD-VI), and further validated by experimental results. Highlights: A 2-D isolator with n-layer Scissor-Like Structure (SLS) is modeled and studied. The system can achieve good isolation performance in two directions simultaneously. An excellent anti-resonance frequency band can be achieved with tunable properties. Experimental results validate the excellent nonlinear stiffness and damping performance.